2023
DOI: 10.1371/journal.pone.0283441
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Cassiopea species identity in the Florida Keys: Cassiopea xamachana and Cassiopea andromeda coexist in shallow waters

Abstract: The phylogeny of the Upside-Down Jellyfish (Cassiopea spp.) has been revised multiple times in its history. This is especially true in the Florida Keys, where much of the Cassiopea stock for research and aquarium trade in the United States are collected. In August 2021, we collected 55 Cassiopea medusae at eight shallow water sites throughout the Florida Keys and sequenced COI, 16S, and 28S genes. Mitochondrial genes demonstrate that the shallow waters in Florida are inhabited by both Cassiopea xamachana and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…These corals have phenotypic differences consistent with local adaptation of thermal performance (Palumbi et al, 2014). Similarly, either the temperature or the duration of daily maximum temperature in the Atlantic site may not be sufficient to induce increased thermal tolerance (either via acclimation or local adaptation).While our COI data revealed that all animals used in this study are C. xamanchana, (consistent with sequencing results from (Muffett & Miglietta, 2023)), our data is unable to resolve population-level differences or test for local adaptation. Thus, it is possible that Cassiopea sampled from both sites represent the same population and are thus robust to stable and fluctuating temperatures.…”
Section: Environmental History Does Not Shape How Cassiopea Respond T...supporting
confidence: 78%
See 1 more Smart Citation
“…These corals have phenotypic differences consistent with local adaptation of thermal performance (Palumbi et al, 2014). Similarly, either the temperature or the duration of daily maximum temperature in the Atlantic site may not be sufficient to induce increased thermal tolerance (either via acclimation or local adaptation).While our COI data revealed that all animals used in this study are C. xamanchana, (consistent with sequencing results from (Muffett & Miglietta, 2023)), our data is unable to resolve population-level differences or test for local adaptation. Thus, it is possible that Cassiopea sampled from both sites represent the same population and are thus robust to stable and fluctuating temperatures.…”
Section: Environmental History Does Not Shape How Cassiopea Respond T...supporting
confidence: 78%
“…Given the morphological variation and potential for cryptic species among Cassiopea sp ., (Muffett & Miglietta, 2023) the species identity of collected animals was confirmed. DNA isolated from medusae used for the 2022 acute heat stress experiment was used to amplify the COI gene for sequencing.…”
Section: Resultsmentioning
confidence: 84%
“…A total of 55 medusae were collected by wading in eight sites along the length of the Florida Keys in late August 2021 over eight days (see Table 1 for a list of sites). Species identification for each individual is reported in Muffett & Miglietta 2023 and summarized in Supplementary Table S1. At each site, coordinates, temperature, time of day, depth, salinity, and pH were recorded (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…One internal swab was placed in DESS, the other in ethanol, as with external swabs. A section of bell tissue was then collected and placed in ethanol for mitochondrial species confirmation (see Muffett & Miglietta 2023). The size of each medusa was taken, and individual medusae were photographed.…”
Section: Methodsmentioning
confidence: 99%